2021
DOI: 10.1088/1742-6596/1788/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Design of e-modules to stimulate HOTS on static fluid materials with the STEM approach

Abstract: This study aims to develop an e-module to stimulate HOTS on static fluid material with the STEM approach. The research method uses the design of research and development (R&D) using the ADDIE model which consists of five stages, namely: analysis, design, development, implementation, and evaluation. This article reported two stages namely analysis and design. The instrument used in the form of a questionnaire of product needs analysis and practitioners’ validation sheets using a Likert scale. Source of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 7 publications
2
14
0
7
Order By: Relevance
“…The completeness of the contents of the e-module is in the form of a synthesis of issues and materials whose presentation can be viewed using electronic goods (Gavrilenko, 2018;Pratono et al, 2018;Elvarita et al, 2020). A good e-module can be arranged based on students' abilities and has a systematic order of presentation (Jaenudin et al, 2017;Laili et al, 2019;Afriyanti et al, 2021). According to several previous studies from experts (Istuningsih et al, 2018;Sitorus et al, 2019;Hadiyanti et al, 2021) it was found that the use of e-modules can help students effectively absorb the material taught by educators.…”
Section: Introductionmentioning
confidence: 99%
“…The completeness of the contents of the e-module is in the form of a synthesis of issues and materials whose presentation can be viewed using electronic goods (Gavrilenko, 2018;Pratono et al, 2018;Elvarita et al, 2020). A good e-module can be arranged based on students' abilities and has a systematic order of presentation (Jaenudin et al, 2017;Laili et al, 2019;Afriyanti et al, 2021). According to several previous studies from experts (Istuningsih et al, 2018;Sitorus et al, 2019;Hadiyanti et al, 2021) it was found that the use of e-modules can help students effectively absorb the material taught by educators.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of previous studies also stated that HOTS can significantly improve students' abilities (Sidiq et al, 2021;Widana, 2020). Other research findings also state that HOTS can help students in learning (Afriyanti et al, 2021;Harta et al, 2020;Sagala & Andriani, 2019). Based on the transcript, students read the text then use reasoning to be able to interpret the fixed procedure correctly.…”
Section: Discussionmentioning
confidence: 92%
“…The importance of textbooks and other learning and teaching materials (LTM) like video presentations in boosting student learning and performance is well acknowledged around the world because it is important in the teaching-learning process (Gunantar, 2017). Afriyanti et al (2021) stated in their study that learning material is an exploration of the teaching and learning resources. It discusses how video-based learning materials or modules helps students to develop the Higher Order Thinking Skills (HOTS) and it is more interactive in Physical Education (Festiawan & Khurrohman, 2021).…”
Section: Introductionmentioning
confidence: 99%